2003
DOI: 10.1039/b308529e
|View full text |Cite
|
Sign up to set email alerts
|

Flexible dye sensitised nanocrystalline semiconductor solar cells

Abstract: We report here flexible solid-state solar cells based upon dye-sensitised nanocrystalline Al2O3 coated TiO2 films and an I2/NaI doped solid-state polymer electrolyte. Such devices show remarkably high solar-light to electrical energy conversion efficiencies of approximately 5.3% under 10 mW cm-2 AM1.5 illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 12 publications
0
91
0
2
Order By: Relevance
“…This is no longer considered a limitation since several recent studies have shown that intimate polymer/metal-oxide infiltration can be achieved by various approaches. These include heat, [14] dipcoating of mesoporous TiO 2 films, [13,15] spin-casting on ultrathin dip-coated TiO 2 films, [6] in-situ growth of TiO 2 from an organic precursor, [11] and heat treatment of a spin-cast polymer into templated nanostructured TiO 2 substrates. [9] It should be noted that infiltration is a function of the polymer used, and that regioregular poly(3-hexyl thiophene) (RR P3HT) has been found to resist infiltration into mesoporous titania through the coiling of the polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…This is no longer considered a limitation since several recent studies have shown that intimate polymer/metal-oxide infiltration can be achieved by various approaches. These include heat, [14] dipcoating of mesoporous TiO 2 films, [13,15] spin-casting on ultrathin dip-coated TiO 2 films, [6] in-situ growth of TiO 2 from an organic precursor, [11] and heat treatment of a spin-cast polymer into templated nanostructured TiO 2 substrates. [9] It should be noted that infiltration is a function of the polymer used, and that regioregular poly(3-hexyl thiophene) (RR P3HT) has been found to resist infiltration into mesoporous titania through the coiling of the polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the transport of charges in low-temperature sintered TiO 2 electrodes, as well as to suppress the charge transfer at semiconductor-electrolyte interface for flexible (photo)-electrochemical devices, many preparation and post-treatment techniques, such as chemical sintering, [97] electrospray, [98] electrodeposition, [99] treatment of pastes or electrodes with titanium-containing gel/solution, [100] mechanical compression of the semiconductor films, [101] and formation of surface coating on the electrodes [102] have been developed. These techniques mainly strive to increase the interparticle necking area to promote the charge transfer between the nanoparticles, [100,101b] while large amount of the electronic states in the bandgap still remains in the semiconductor.…”
Section: Strain Induced Reduction and Redistribution Of Trap States Amentioning
confidence: 99%
“…The prototype of this family of devices is the dye-sensitized solar cell (DSC), which accomplishes optical absorption and charge separation by combining a light-absorbing material (the sensitizer) with a wide band gap semiconductor of nanocrystalline morphology (O'Regan & Graetzel 1991;Keshner & Arya, 2004). The DSC is used in conjunction with electrolytes (Graetzel 2001), ionic liquids (Wang 2005a), polymer electrolytes (Haque et al 2003) or organic (Bach et al 1998) as well as inorganic hole conductors (O'Regan 1997; Perera et al 2003). Other strategies employ blends of organic materials, such as polymeric (Halls et al 1995) or molecular semiconductors (Peumans & Forrest 2001) as well as hybrid cells using a p-type semiconducting polymer (such as poly 3-hexylthiophene), in conjunction with a fullerene (Brabec et al 2003) or CdSe 'nanorods' (Huynh et al 2002).…”
Section: Mesoscopic Solar Cellsmentioning
confidence: 99%